A QUALIDADE DE VIDA NO TRABALHO DOS PROFESSORES EM UMA INSTITUIÇÃO PARTICULAR DE ENSINO - Alves, Joemar Braga (2009)
The present work has as object demonstrates the perceptions of life quality in the academical teachers' work being used the models of competences for the organizational well-being the Abordagem Biopsicossocial (BPSO). In the study in subject a descriptive exploratory research was accomplished at a certain university that was chosen for the development of the research. The study was characterized as descriptive, looking for, of this sorts things out, to identify the variables that determined the criteria of life quality in the work in the teachers' of the higher education perception. A research "survey" was used, that it can be considered as the collection of data on characteristics, actions or opinions certain grupamento of people, through an instrument of collection of data. The result will show as those teachers notice the life quality in the work, in other words, in way positive or negative and in that subjects or factors are the main deficiencies that can be, for instance, health, career, condition socioeconomic or other more considered in the research.